Natural occurrence of Wolbachia in Anopheles sp. and Aedes aegypti populations could compromise the success of vector control strategies - Gnankine, Olivier; Dabiré, Roch Kounbobr (Frontiers in Tropical Diseases, 2024)
Wolbachia is a maternally inherited bacterium commonly detected in approximately 50% of arthropod species, including mosquito vector species. Wolbachia species have been detected in different mosquito vectors, but in most malaria vectors, their occurrence in natural populations were reported 10 years ago. Aedes aegypti, the main vector of dengue virus, is generally uninfected by Wolbachia, and records of infection are rare and only include a few populations. This bacterium impacts the biology, ecology, and evolution of vector populations. Wolbachia has attracted considerable interest because of its role in reducing disease transmission. Moreover, this bacterium is known to manipulate insect reproduction by inducing cytoplasmic incompatibility (CI), thus providing new avenues for vector control strategies. Interestingly, wMel or wAlbB Wolbachia infections in Aedes populations exhibit a stable high frequency in most areas and contribute to the reduction of local dengue transmission. In natural populations of Anopheles, although Wolbachia was found, little is known about its role and effect on Plasmodium. If the incompatible insect technique (IIT) and population replacement strategy resulted in significant decreases in the dengue transmission in endemic countries such as the USA, Taiwan, Australia, and Brazil, natural Wolbachia detection in mosquitoes may pose a threat to these vector control strategies, raising the following question: “Does the natural occurrence of Wolbachia in Anopheles sp. and Ae. aegypti populations compromise the success of vector control strategies? This review presents recent achievements of Wolbachia in natural Anopheles and Ae. aegypti populations in terms of prevalence and provides guidelines for the development of Wolbachia-based vector control.